(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Too many female gynaecological issues are a result of shifting food habits and lifestyles. One of the main concerns for women who are of reproductive age is uterine fibroids. The symptoms of uterine fibroids have a detrimental effect on women’s well-being, their ability to engage in social and physical activities, and their productivity at work. A 25-year-old married female patient arrived at the outpatient clinic complaining of lower abdominal pain, heavy menstrual flow, burning during micturition, and white discharge coming from her vagina six months ago . An intrauterine fibroid measuring 24 x 10 mm size with an ET of 10.5 mm was seen during the ultrasound examination. The ovaries’ B/L measurements were normal, and the wall of the gallbladder was slightly enlarged. Surgery was recommended for the same condition, but the patient refused to have it done and preferred non-hormonal treatment. The patient refused to take any allopathic medication. The patient sought Ayurvedic treatment at the OPD. She received treatment in accordance with the Ayurvedic regimen prescribed by Kanchanar Guggulu, Kuberaksha vati, Raktavardhak vati, Ashoka-arishta, Hingwashtak churna, Chandraprabha vati, Kumaryaasawa.After three months of treatment and a follow-up every 15 days, a repeat scan showed normal results and symptom alleviation.